KECANDUAN GAME ONLINE DAN MASALAH-MASALAH YANG DIALAMI SISWA DI SMA NEGERI 12 PEKANBARU - Sari, Mariaty Indah; Rosmawati, Rosmawati; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Based on observations and discussions with counceling and guidence teachers in SMA Negeri 12 Pekanbaru encountered the phenomenon: playing online games performed by students both male and female students. Online gaming is found almost all over the android and smartphone students. The intensity of playing the students' online games is different. From a class that has androin found at least 1 to 2 students who are addicted to playing online games on their handphones. There is also a saying that playing online games is as fun as playing with peers. The purpose of this study was to determine the description of the students addicted to online games and the problems experienced by students addicted to online games in SMA Negeri 12 Pekanbaru. Based on the results of the initial questionnaire was found that students who addicted to online games amounted to 33 students. Sampling technique used in this research is purposive sampling technique that is sample with consideration. Based on the result of the research, it can be concluded that: Addiction of online game among SMA is known more than half is in the aspect of salience, euphoria, conflict, and tolerance, almost half of students are in withdrawal and relapse and reinstatement aspects. Nearly half of students have Advanced Social and Education Relationship problems and the future, over a quarter of students have problems with the physical and health aspects, leisure, and careers and jobs.Keywords: Online Game Addiction, Student Problems